The chlorinated ethylenes : their hepatic metabolism and carcinogenicity - Costa, Anita Kathleen (Division of Medical Biochemistry, 2026)
Following the observation that vinyl chloride monomer was activated into potentially carcinogenic species by the hepatic cytochrome P-450 enzyme system, widespread interest was generated in the metabolism of the other chlorinated ethylenes. The chlorinated ethylene~5 which were investigated herein included vinylidene chloride which is used for the manufacture of Saran plastics; cisand trans-I, 2-dichloroeth ylene and tetrachloroeth ylene, which are industrial solvents; and trichloroethylene which is a volatile anaesthetic agent. An investigation of the hepatic metabolism and potential carcinogenicity of the chlorinated ethylenes is reported in this thesis. The hepatic metabolism of these compounds was primarily investigated using two different liver preparations, viz. hepatic microsomal preparations and freshly isolated hepatocytes, although partially purified cytochrome P-450 was used in one case, viz. trichloroethylene. Hepatic microsomes were utilized to investigate Phase I of xenobiotic metabolism by the cytochrome P-450 enzyme system, while the isolated hepatocytes were utilized as a system for assessing the metabolism of the chlorinated ethylenes which might prov~de a better representation of the in vivo situation since these cells contain the enzymes of both Phase I and Phase II of xenobiotic metabolism. Furthermore, the hepatocytes provide a :,otentiall y advantageous system for testing chemically-induced DNA repair synthesis in order to measure the carcinogenic potential of -.:hemicals that require activation by the liver. The chlorinated ethylenes were found to be metabolized by vi hepatic cytochrome P-450 as observed from ( i} their production of a Type I difference spectrum with hepatic mlcrosomes; (ii) their ability to stimulate hepatic microsomal CO-inhibitable NADPH oxidation; and (iii) th•~ requirements for their conversion to chlorinated metabolites being hepatic microsomes, NADPH-generating system and substrate. (iv) specific inhibitors of cytochrome P-450 diminished or eliminated metabolite production by hepatic microsomal incubation mixtures. It was found that the forms of hepatic microsomal cytochrome P-450 elevated by phenobarbital and the forms found in untreated animals, not inducible by phenobarbital or by the polycyclic hydrocarbons, were involved in the metabolism of the chlorinated ethylenes. Cytochrome P-450c, which is induced by pretreatment with polycyclic hydrocarbons, appeared to play no role in the metabolism of any of the chlorinated ethylenes in vitro. The major metabolites of the chlorinated ethylenes following incubation in the presence of hepatic microsomes and a NADPHgenerating system were as follows: Vinylidene chloride, chloroacetate and dichloroacetaldeh yde; cis- and trans-I, 2-dichloroethylene, dichlo:roacetaldeh yde; trichloroeth ylene, chloral hydrate; and tetrachloroeth ylene, trichloroacetate. The abovementioned metabolites ·were generally found in isolated hepatocytes in the presence of the chlorinated ethylenes, but in some cases, there was extensive secondary :ietabolis:n of the major metabolites observed in hepatic microsomes, vii e.g. following vinylldene chloride and trans-1,2-dichloroethylene metabolism in isolated hepatocytes, only trace amounts of dichloroacetaldehyde were seen. In isolated hepatocytes, dichloroacetaldehyde was extensive! y converted to 2, 2-dichloroethanol and dichloroacetic acid by the cytosolic alcohol and aldehyde dehydrogenase, respectively. Chloral or its hydrated analogue, chloral hydrate, the sole metabolite of trichloroethylene in hepatic microsomes, was also converted to 2 ,2, 2-trichloroethanol and trichloroacetic acid in the presence of isolated hepatocytes. The issue is, however, further complicated by the observation that the levels of many of the chlorinated metabolites decreased with time in hepatic suspensions; perhaps in part due to their incorporation into physiological pathways, e.g. chloroacetate into chlorocitrate. It was found that the extent and position of chlorination of the chlorinated ethylenes appears to play a very important role in the hepatic management of the chlorinated ethylenes in the short term, i.e. the rates of metabolite production and which form of cytochrome P-450 is involved; and in the long term, i.e. their carcinogenic potential, for example 1 i). Cytochrome P-450b and the form of cytochrome P-450 found in untreated rats (and not inducible by phenobarbital or polycyclic hydrocarbons) play an increasing and decreasing role, respect! vel y, in the metabolism of the chlorinated ethylenes as the extent of chlorination increases. ii). It was observed that the chlorinated ethylenes with the greater degree of symmetry, e.g. tetrachloroethylene and trans-1, 2-dichloroethylene, were metabolized at a lower rate viii than those chlorinated ethylenes with relatively fewer degrees of symmetry, e.g. trichloroethylene and cis-1,2- dichloroethylene. iii). The degree of symmetry also plays a role in the ability of the chlorinated ethylene to "uncouple" the cytochrome P-450 enzyme system. cis-1,2-Dichloroethylene and vinylidene chloride, which each possess relative! y fewer degrees of symmetry, act as uncouplers with the subsequent production of H2 o2 , while trans-!, 2-dichloroethylene and tetrachloroeth ylene, with higher degrees - of symmetry, do not. iv) • The ability of the chlorinated ethylenes to cause the degradation of cytochrome P-450 is Ii nked to the chemical nature of the major rearrangement product of the proposed epoxide intermediate. The epoxides that rearrange exclusively to aldehydes in hepatic microsomes correspond to chlorinated ethylenes that modify the heme of cytochrome P-450, viz. els- and trans-1, 2-dichloroethylene and trichloroethylene, while the epoxides that rearrange to an acyl chloride or to both an aldehyde and an acyl chloride are from chlorinated ethylenes that do not modify the heme of cytochrome P-450, viz. vinylidene chloride and tetrachloroethylene. ,, ) . The ability of the chlorinated ethylenes to induce DNA repair synthesis in a mamnaliah test system appears to provide an indication of their carcinogenic potential. Vinylidene chloride, cis1, 2-dichloroethylene and trichloroethylene gave rise to DNA repair in isolated rat hep a toe ytes, while trans-!, 2-dichloroeth ylene and tetrachloroethylene did not. This ability ix shows a positive correlation with a relatively lower degree of symmetry and/or their ability to cause H2 o2 production. A good correlation appears to exist between the ability of the chlorinated ethylenes to induce DNA repair in isolated hepatocytes and their reported carcinogenicity 1£ vivo. An exciting observation was that the els-isomer of the 1, 2- dichloroethylenes, both of which are considered to be noncarcinogenic, gave rise to DNA repair, while the transisomer did not.